STUDENTS’ ATTRIBUTIONS ON ENGLISH READING SKILL IN AVIATION FIELD - Maria Asumpta Deny Kusumaningrum; Made Frida Yulia (ELTR Journal, 2021)
Learning activities have a close relation with progress, achievement or even failure. Attribution is the clarifications and reasons that individuals give for advance, accomplishment, and indeed disappointment towards something they have experienced, especially in their language learning. This study aims to investigate the students’ attributions on their English-reading skill especially in reading aviation text. Thus, we know the progress, the achievement and also the failure of the learning activity in students’ reading skill. The participants of the study were sixty-nine students who took Bahasa Inggris Teknik II class. Open-ended questionnaire and interview were used as the instruments to collect the data. The results showed that interest was the major attributions for doing well and ability was the major factor for not doing well.